Determinants of collective action for sustainable natural resource management in Haramaya District of Ethiopia - Hassen Jemal Yousuf (University of Cape Coast, 2011)
The study set out to assess determinants of collective action fbr sustainable natural resource management in the Haramaya District of Ethiopia. It employed a combination of purposive and random sampling techniques to select three representative sites in the district and interviewees fbr the first phase community level survey and 180 sampled respondents fbr second phase household level survey respectively. The primary data were collected using both qualitative and quantitative approach. Description of verbal expression of respondents, interpretation and appreciation of facts were used fbr the qualitative data analysis. Simple descriptive statistics were used to analyze the quantitative data. The study revealed an increasing level of natural resource scarcity and degradation over time implying the need fbr collective action among different resource users. However, the likelihood of collective action among resource users was found less likely to happen mainly due to dwindling social capital (trust) among resource users, low support of institutional (endogenous and exogenous) arrangements, and differences among resource users (farm proximity to commons). Furthermore, low level of past collective action experience, low understanding of the resource situation 一 perceived level of natural resource degradation and natural resource interdependencies - and required coordinated action among resource users to overcome natural resource degradation were found to have reasonably contributed to the low likelihood of collective action. The research, thus, recommends the need fbr institutional policy reibrni and the enhancement of community awareness about the natural resource situation and the required collective action.
xviii,249p:,ill